2010
DOI: 10.1590/s0103-84782010005000019
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic and ecobiometric findings in the eyes of adult goats

Abstract: The knowledge of the normal appearance and ocular dimensions of goat eyes facilitates the use of ultrasonography in the evaluation of ocular disease. The objective of the present study was to determine ultrasonographic and ecobiometric findings in the eyes of adult goats. B- and A-mode ultrasonography was performed in 30 healthy adult goats (60 eyes) (n=5 intact females and n=15 castrated males). Ultrasonography was performed after instillation of a topical anesthetic. Lubricating jelly was placed on the 20MHz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…No significant differences were found between the right and left eyes. Ribeiro et al (16) showed that ocular measurements in the right and left eyes were not significantly different, and the same result was obtained with males and females of adult goats. Studies have demonstrated a dependence of the morphological structure of the corneal parameters on animal species (11,13,14), the habitat of the species (2,12,14) and environmental conditions of animals (14).…”
Section: Resultsmentioning
confidence: 53%
“…No significant differences were found between the right and left eyes. Ribeiro et al (16) showed that ocular measurements in the right and left eyes were not significantly different, and the same result was obtained with males and females of adult goats. Studies have demonstrated a dependence of the morphological structure of the corneal parameters on animal species (11,13,14), the habitat of the species (2,12,14) and environmental conditions of animals (14).…”
Section: Resultsmentioning
confidence: 53%
“…It is important to consider the limitations of our study as well as its strengths. We used goat eyes in this study, which are similar to human eyes in general eye size and shape [59]. However, there are also distinct differences.…”
Section: Discussionmentioning
confidence: 99%
“…Animals such as rats [61][62][63][64][65], rabbits [20,61,[66][67][68], pigs [69,[70][71][72], mice [26,27,61,73,74], dogs [31,75,-78]), and goats [18,79,80] have been used as in vivo models of infection in previous studies. Alternative methods that are viable and eliminate pain to animals have been encouraged [51][52][53][54][55][56][57][58][59][60].…”
Section: Introductionmentioning
confidence: 99%